Software Language Engineering First International Conference, SLE 2008, Toulouse, France, September 29-30, 2008. Revised Selected Papers - Gaaevi<U+0007>, Dragan.; Lm̃mel, Ralf.; Wyk, Eric. (Lecture Notes in Computer Science, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Conference on Software Language Engineering, SLE 2008, held in Toulouse, France, in September 2008. The 16 revised full papers and 1 revised short paper presented together with 1 tool demonstration paper and 2 keynote lectures were carefully reviewed and selected from 106 initial submissions. The papers are organized in topical sections on language and tool analysis and evaluation, concrete and abstract syntax, language engineering techniques, language integration and transformation, language implementation and analysis, as well as language engineering pearls.